Ks. Mirosław Kowalczyk, U początków teologii historii w Polsce. F. Sawicki, K. Michalski, A. Pechnik, Wyd. KUL, Lublin 2008, ss. 418. - Góźdź, Krzysztof (Teologia w Polsce, 2020)
Recenzja książki: Ks. Mirosław Kowalczyk, U początków teologii historii w Polsce. F. Sawicki, K. Michalski, A. Pechnik, Wyd. KUL, Lublin 2008, ss. 418.